THE PROBLEM OF CEUTA AND MELILLA IN SPANISH FOREIGN POLICY - Ekaterina Cherkasova (Ибероамериканские тетради, 2017)
The article is dedicated to one of the most important problems of Spain’s foreign policy, namely the problem of the two Spanish enclaves located on the territory of Morocco - Ceuta and Melilla. The historical and legal provisions form the basis of arguments of the Spanish and Moroccan parts justifying their claim to these disputed territories. A comparison is made between the problems of Ceuta and Melilla and Gibraltar.Particular attention is paid to the question of whether they are covered by NATO’s security guarantee. The author substantiates that Morocco is using the issue of Ceuta and Melilla as a means of pressure on Spain to get beneﬁts in other areas, including trade, immigration, and ﬁshing. Rabat also seeks to force Spain to change its position on the Western Sahara. The current situation of the Spanish cities in the light of their current economic, migratory and political problems is analyzed. It isemphasized that illegal immigration mostly from sub-Saharan countries is one of the main problems of the Spanish-Moroccan relations, complicating the situation in Ceuta and Melilla. This problem is far from being resolved. The main task of the Western countries regarding this issue is the maintenance of stability in the region, which perfectly meets the interests of Spain. Madrid’s eﬀorts are focused primarily on prevention of such development of political and economic situation which would put the country before the need to strengthen its southern border by military means. This strategic objective has become particularly relevant in light of recent events in North Africa.